(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to build a training program according to the Briggs model for teachers of mathematics, based on the need of the educational field and to enable the teacher to keep pace with challenges and developments and to become more responsible in society. The researcher believes that it is necessary to train mathematics teachers on modern models in educational design, and accordingly, the training program was built with three steps (planning, implementation, evaluation) and the use of feedback for each of its steps according to the Briggs model, which consists of ten main steps (identifying needs, Organizing the course, writing goals, preparing evaluations, analyzing goals, designing a strategy, designing lessons, formative evaluation, final content, final evaluation)